The Impact of Work Family Conflict on Turnover Intention: A Study of Married Gen Z Banking Employees in Indonesia with Burnout and Job Satisfaction as Mediators - Yupentus Bio Samuel; Ramadania; Dody Pratama Marumpe; Ilzar Daud; Mazayatul Mufrihah (Al-Qalam Institue, 2026)
This study aims to analyze the effect of work family conflict on turnover intention among married Generation Z employees in the banking sector, with burnout and job satisfaction serving as dual mediating variables. A quantitative approach was employed by distributing online questionnaires to 200 married Gen Z banking employees in Indonesia, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The results indicate that work–family conflict has a positive and significant effect on turnover intention, although its direct contribution is relatively small. However, work–family conflict exerts a strong and significant influence on increasing burnout and decreasing job satisfaction. Among the variables examined, job satisfaction emerged as the most dominant predictor in reducing turnover intention, demonstrating the highest path coefficient. Furthermore, the mediation analysis confirms that burnout and job satisfaction function as significant emotional mechanisms that translate work–family conflict into turnover intention, with the mediating role of job satisfaction being substantially stronger than that of burnout. These findings imply that maintaining and enhancing job satisfaction is a critical talent retention strategy, particularly in mitigating the adverse effects of work–family conflict among married Gen Z employees in the banking industry.